Influencia del internet y juegos en red en el desarrollo de habilidades comunicativas en los estudiantes de 8 a 11 años de la Escuela Sulima García Valarezo periodo lectivo 2014-2015. - Neira Morales, Lissette (2015)
This research work has a focus analytical 11 year of school ―Sulima Garcia Valarezo‖, teaching period 2014 – 2015 once detected the problem thanks to exploratory research is boilding the theoretical based on information framework. Collect of books, leaftlet, magazines and net in this way properly based variables of this study.